Microbial Contamination and Antimicrobial Resistance Profiles Indicate Potential Risks of Infection at the Veterinary Medical Teaching Hospital - UFRGS, Porto Alegre, Brazil - Giacon, Mariana Muller; Siqueira, Franciele Maboni; da Motta, Amanda de Souza (Acta Scientiae Veterinariae, 2021)
Background: This study aimed to assess the level of bacterial contamination in the Small Animals Sector of the Veterinary Medical Teaching Hospital (HCV) of the Universidade Federal do Rio Grande do Sul (UFRGS). Firstly, a committee was invited to complete a questionnaire and to list critical sample sites for collection. With the identification of the places to be sampled, collections were made with sterile swabs on different surfaces of environments of the Veterinary Hospital. The identification of important bacteria in the veterinary area, in the different sampled environments, raises the concern for hygiene procedures in the veterinary hospital environment. Materials, Methods & Results: Sixteen samples were collected from these different areas, and microbiological analyses were performed. Standard counts of viable and strictly aerobic mesophilic microorganisms were realized. Collections were made to assess ambient air quality. With the microbiological analysis performed, bacteria of clinical importance were identified. To assess the resistance profile of the bacteria, the susceptibility test to antimicrobials was performed. MALDI-TOF/MS measurement identified 29 bacteria at the genus level and 10 bacteria at the species level and the antimicrobial susceptibility test was realized. Most of the isolates identified (60%) were bacteria of the genus Staphylococcus spp. Regarding antimicrobial susceptibility analysis the 10 bacteria identified at the species level were assessed. Test results showed that the isolates S. aureus, S. epidermidis and S. haemolyticus - collected from treatment room 2 - and S. haemolyticus, which had been isolated from samples from treatment room 2 of the cattery, presented multiresistance. Pantoea ananatis isolates from room 5 also showed a multiresistant profile for erythromycin, cephalothin, vancomycin and ampicillin. Micrococcus luteus isolates from the x-ray room and the kennel showed resistance to ceftazidime. Staphylococcus equorum isolates from room 4 were sensitive to all tested antimicrobials. Discussion: In Brazilian legislation there are no official microbiological parameters for surfaces in a veterinary hospital environment. The microorganisms present in the air are transient and variable, and the number and types of airborne agents is determined by the various sources of contamination in the environment. These microorganisms can be found in suspension, particulate matter and water droplets. Veterinary medical care tables are potentially contaminated by the animals handling, including those that sometimes defecate or urinate during their medical visit. Frequent handwashing is also known to be an important means of personal protection and disease prevention, although it is estimated that only 40% of practitioners do so routinely. Based on these results, we recommend a plan of bacterial control and disinfection that should be implemented to ensure more effective sanitary conditions. Microorganism counts were high in some of the veterinary hospital environments tested, indicating that current disinfection and hygiene practices are not sufficient to control the establishment of these microorganisms at the study sites. In view of this, it is reasonable to conclude that permanent monitoring and assessment of the effectiveness of hygiene protocols is needed in different sectors of the hospital. This may be an essential tool in a preventive approach to stop the spread of selectively resistant microorganisms, as well as cases of hospital infections. In addition, continuous staff training and awareness of the importance of personal and environmental hygiene is vital for minimizing the presence of these microorganisms in hospitals and avoid their transmission to patients. Finally, a more systematic hygiene guideline should be implemented in areas that showed higher counts.